Study on the change monitoring of typical estuarine wetland and its effect on ecological factors in Bohai Rim region, China - Li, Xiaodong; Liu, Ge (Frontiers in Ecology and Evolution, 2022)
Estuarine wetlands provide an especially ecological home for various flora and fauna, with fragile ecological structures and functions easily affected by the external disturbances of both anthropogenic and natural activities. Recently, wetlands of the Bohai Rim Region have been, and continue to be, lost or altered under the influence of both local urbanization and economic development. There is an increasing need for crucial essential wetland change detection as one of the most critical works for relevant research. The paper's objective focuses on detecting the annual and interannual changes at a large spatial scale for understanding the mainly changed cover type of estuarine wetlands and measuring its impact on coastline ecological factors. Two typical study areas, including the Shuangtai Estuary wetland and Yellow River Delta, are selected for the assessment of changes to wetlands in Bohai Rim Region, China. Additionally, Landsat TM/OLI images between 2005 and 2015, as the standard years for change detection, are used as the experimental data resources. Based on the Remote Sensing base Ecological Index (RSEI), three ecological indexes include water body index, vegetation index, and soil index, calculated the annual maximum difference and the inter-annual dynamic rate of change to wetland. Furthermore, wetland changes are graded and evaluated five significant levels from the annual yearly and interannual scales. Results show several significant findings: (1) from 2005 to 2015, the ecological change with an overall improvement trend was in two monitoring areas of Bohai Rim Region. The annual change of ecological factors in the positively changed area (improve) was more and more significant, with the mainly converted type of the expansion of paddy field. In the negatively changing area (degrade), annual ecological change was more and more insignificant, with the main expansion of bare land. (2) The significantly increased accumulation of NDVI was the main ecological change feature of the Shuangtai Estuary wetland. The significant regional changes in the Yellow River Delta were the interaction of ecological factors, included MNDWI, NDVI, and NDSI. The study on the change detection of wetland and its influence on ecological factors in Bohai Rim Region.